2012
DOI: 10.1186/1757-7241-20-23
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of defibrillation and cardiopulmonary resuscitation performance during simulated cardiac arrest in nursing student teams

Abstract: BackgroundAlthough nurses must be able to respond quickly and effectively to cardiac arrest, numerous studies have demonstrated poor performance. Simulation is a promising learning tool for resuscitation team training but there are few studies that examine simulation for training defibrillation and cardiopulmonary resuscitation (D-CPR) in teams from the nursing education perspective. The aim of this study was to investigate the extent to which nursing student teams follow the D-CPR-algorithm in a simulated car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
6
0
4
Order By: Relevance
“…Reaction times of defibrillation were defined as the time from discovery of unconsciousness until shock was delivered. 18 We performed a paired t-test to compare the reaction times of first simulation and second simulation scores in all groups, method A and B groups. We performed the Student's t-test to compare the reaction times of the first CPR simulation and second CPR simulation, and the differences in method A and B groups.…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction times of defibrillation were defined as the time from discovery of unconsciousness until shock was delivered. 18 We performed a paired t-test to compare the reaction times of first simulation and second simulation scores in all groups, method A and B groups. We performed the Student's t-test to compare the reaction times of the first CPR simulation and second CPR simulation, and the differences in method A and B groups.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Future studies should be conducted with two independent assessors. 18 Finally, our CPR video was from the year 2005. During the resuscitation training, we followed the updated CPR guidelines.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Although this type of training has evolved to the current state over the years, essentially the model itself has been unchanged. Also, in the current CPR guidelines, teamwork issues have impacted the recommendations [4-7], although clarifications of what characterizes effective teamwork during CPR are lacking [8]. …”
Section: Introductionmentioning
confidence: 99%
“…14,25,27 Furthermore, previous studies on nursing students reported that performance according to guidelines was poor when a CPR situation was tested in a simulation laboratory. 10,14,28 Systematic literature reviews further revealed that the number of chest compressions, depth and position of compression, position of hands, and maintenance of respiratory tract were particularly poor. 29 Self-efficacy, high-level problem solving, and actual performance skills for patient care in emergency situations are necessary for professional nurses to yield positive patient outcomes.…”
mentioning
confidence: 96%